Emotional Regulation and Toxic Relationships in Late Teens Who Date - Fauzia Herdiani, Rizka; Rahmat Hidayat, Dede (Rifa'Institute, 2023)
Introduction: In dating individuals will be faced with problems in relationships where not a few individuals solve them with acts of violence. Dating violence is an indication that refers to a toxic relationship. Objective: to test whether emotional regulation is related to the level of toxic relationships in dating relationships in late adolescents dating in Bekasi City. Method: This study uses a quantitative approach with a correlational method. The instruments used to collect the data were the emotion regulation scale and the toxic relationship scale. The data were analyzed by non-parametric test techniques using spearman non-parametric correlation test. Result and Discussion: A result of -0.483** and a significance result of <0.001 (p<0.01). Conclusions: This study shows the correlation of the two significant variables and produces a negative correlation direction. The higher a person's emotional regulation, the lower the level of toxic relationships, and vice versa.